Do Dogs Prefer Helpers in an Infant-Based Social Evaluation Task? - McAuliffe, Katherine; Bogese, Michael; Chang, Linda W.; Andrews, Caitlin E.; Mayer, Tanya; Faranda, Aja; Hamlin, J. Kiley; Santos, Laurie R. (Frontiers in Psychology, 2019)
Social evaluative abilities emerge in human infancy, highlighting their importance in shaping our species’ early understanding of the social world. Remarkably, infants show social evaluation in relatively abstract contexts: for instance, preferring a wooden shape that helps another shape in a puppet show over a shape that hinders another character (Hamlin et al., 2007). Here we ask whether these abstract social evaluative abilities are shared with other species. Domestic dogs provide an ideal animal species in which to address this question because this species cooperates extensively with conspecifics and humans and may thus benefit from a more general ability to socially evaluate prospective partners. We tested dogs on a social evaluation puppet show task originally used with human infants. Subjects watched a helpful shape aid an agent in achieving its goal and a hinderer shape prevent an agent from achieving its goal. We examined (1) whether dogs showed a preference for the helpful or hinderer shape, (2) whether dogs exhibited longer exploration of the helpful or hinderer shape, and (3) whether dogs were more likely to engage with their handlers during the helper or hinderer events. In contrast to human infants, dogs showed no preference for either the helper or the hinderer, nor were they more likely to engage with their handlers during helper or hinderer events. Dogs did spend more time exploring the hindering shape, perhaps indicating that they were puzzled by the agent’s unhelpful behavior. However, this preference was moderated by a preference for one of the two shapes, regardless of role. These findings suggest that, relative to infants, dogs show weak or absent social evaluative abilities when presented with abstract events and point to constraints on dogs’ abilities to evaluate others’ behavior.